معاییر الاعتماد فى برامج علوم المکتبات والمعلومات فى ضوء المعاییر الدولیة : دراسة تحلیلیة - د. اسماء صلاح على (المجلة الدولية لعلوم المكتبات والمعلومات)
Academic accreditation systems Contribute to determining the extent towhich educational institutions achieve their goals and identify strengths to bestrengthened and shortcomings to work to overcoming them, Accreditation is ascientific institutional activity directed towards the advancement and upgrading ofeducational institutions and study programs, and it is an effective and influentialtool to ensure the quality of the educational process and its output quality andcontinuity of development, This study aims to shed light on the importance ofacademic accreditation for library and information programs, identify the mostimportant international standards for science libraries and information, and thestudy will focuses on the accreditation standards used in the library andinformation departments in Egypt, and examine the role of the national Authorityfor Quality Assurance and Accreditation of Education (NAQAAE) in Egypt,Finally, the criteria and stages of program accreditation will be presented.In order to achieve the objectives of the study will depend on the study,descriptive and analytical approach that deals with the collection, information andfacts, analysis and interpretation